2023
DOI: 10.3390/tropicalmed8010056
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Geographical Variation in Plasmodium knowlesi Apical Membrane Protein 1 (PkAMA-1) on Invasion Dynamics of P. knowlesi

Abstract: Plasmodium knowlesi has emerged as an important zoonotic parasite that causes persistent symptomatic malaria in humans. The signs and symptoms of malaria are attributed to the blood stages of the parasites, which start from the invasion of erythrocytes by the blood stage merozoites. The apical membrane protein 1 (AMA-1) plays an important role in the invasion. In this study, we constructed and expressed recombinant PkAMA-1 domain II (PkAMA-1-DII) representing the predominant haplotypes from Peninsular Malaysia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Hence, this serves as a determinant of a vaccine candidate for human knowlesi malaria. Recently, Ng et al (2023) found that rabbit-raised antibodies against the region II of pkama-1 displayed significant differences when compared to the negative control group, with close to 50% invasion inhibition [ 56 ]. The findings by Muh and colleagues (2018) are similar but with a lower antibody concentration used [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this serves as a determinant of a vaccine candidate for human knowlesi malaria. Recently, Ng et al (2023) found that rabbit-raised antibodies against the region II of pkama-1 displayed significant differences when compared to the negative control group, with close to 50% invasion inhibition [ 56 ]. The findings by Muh and colleagues (2018) are similar but with a lower antibody concentration used [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both Pk and Pf merozoites use Apical Membrane Antigen 1 (AMA1 or AMA-1) to reorient the parasite's apical end toward the host cell [45,46]. Anti-PkAMA1 IgG antibodies can block Pk invasion into human RBCs in vitro [47].…”
Section: Rbc Invasionmentioning
confidence: 99%